Analysis of the social network of a Center for Psychosocial Attention for alcohol and other drugs - Débora Schlotefeldt Siniak; Leandro Barbosa de Pinho; João Nunes Maidana Júnior; Marciele Barcelos Ávila; Vanessa Alvez Mora da Silva (Universidade Federal de Santa Maria, 2021)
Objective: to investigate the social networking of a Center for Psychosocial Attention for alcohol and other drugs (CAPS AD) from referrals and case receipts. Method: quantitative, descriptive, developed in a municipality of the State of Rio Grande do Sul, Brazil.  Data was collected from August to December 2017, by means of a yarning circle, application of a questionnaire in a Likert Scale format, and construction of sociograms, reviewed by Social Networking Analysis; 13 professionals participated in the research. Results: there were 37 actors directly or indirectly involved in caring for people who use drugs. CAPS AD and the Family Health Strategy are some of the main services that refer and receive demands from this population. Conclusion: Decentralization of the network and connectivity among the actors are necessary, and ways of working together to build an integrated and cooperative system must be considered.